Comparative Numerical and Experimental Analyses of Conical Solar Collector and Spot Fresnel Concentrator - Haedr Abdalha Mahmood Alsalame; Kang Kyeong Sik; Gwi Hyun Lee (Energies)
This paper aims to compare the thermal performances of the conical solar collector (CSC) system and the spot Fresnel lens system (SFL) using water and CuO nanofluid as the working fluids. The studied CFD models for both systems were validated using experimental data. At an optimal flow rate of 6 L/min, the SFL system showed higher optical and thermal performance in comparison with that of the CSC system. In the case of the SFL system, the availability of a greater amount of solar energy per unit collector area caused an increase in thermal energy. Moreover, in the case of the CSC system, the non-uniform distribution of solar flux on the absorber’s outer surface leads to an increase in temperature gradient and heat losses. As a heating medium, the CuO nanofluid outperformed the water in terms of higher thermal conductivity and heat capacity. The average thermal efficiencies of 64.7% and 61.2% were achieved using SFL with and without CuO nanofluid, respectively, which were 2.4% and 0.5% higher than those of the CSC with and without nanofluid. CFD simulations show a 2.80% deviation for SFL and 2.92% for CSC, indicating acceptable accuracy compared to experimental data.